2016
DOI: 10.1158/1078-0432.ccr-15-0829
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of KRAS-Mutant Colorectal Cancers to Combination Therapy That Cotargets MEK and CDK4/6

Abstract: Purpose The emerging need for rational combination treatment approaches led us to test the concept that co-targeting MEK and CDK4/6 would prove efficacious in KRAS mutant (KRASmt) colorectal cancers, where upregulated CDK4 and hyperphosphorylated retinoblastoma (RB) typify the vast majority of tumors. Experimental Design Initial testing was carried out in the HCT-116 tumor model, which is known to harbor a KRAS mutation. Efficacy studies were then performed with five RB+ patient-derived colorectal xenograft … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 27 publications
8
49
0
Order By: Relevance
“…Given these concerns, our data demonstrated preclinical efficacy of combination MEK and CDK4/6 inhibitors in RAS-mutant CRCs. This data also complements the recent report of the combination of palbociclib and trametinib in KRAS -mutant CRC PDX models [63], but demonstrates that inhibition of phospho-S6 is a potential pharmacodynamic biomarker, and uniquely demonstrates that this inhibition is synergistic with the combination of CDK4/6 and MEK inhibitors in a broader number and mutational diversity of cell lines, including “atypical” KRAS A146T mutant CRC PDX models. Our data has justified development of a planned phase II clinical trial of the combination in patients with refractory metastatic RAS-mutant CRC.…”
Section: Discussionsupporting
confidence: 86%
“…Given these concerns, our data demonstrated preclinical efficacy of combination MEK and CDK4/6 inhibitors in RAS-mutant CRCs. This data also complements the recent report of the combination of palbociclib and trametinib in KRAS -mutant CRC PDX models [63], but demonstrates that inhibition of phospho-S6 is a potential pharmacodynamic biomarker, and uniquely demonstrates that this inhibition is synergistic with the combination of CDK4/6 and MEK inhibitors in a broader number and mutational diversity of cell lines, including “atypical” KRAS A146T mutant CRC PDX models. Our data has justified development of a planned phase II clinical trial of the combination in patients with refractory metastatic RAS-mutant CRC.…”
Section: Discussionsupporting
confidence: 86%
“…However, many genes in these regions are not eligible as candidate genes with major roles in colorectal carcinogenesis. Of the many candidate genes, we identified cyclin‐dependent kinase (CDK) 4/6 on 12q14.1–14.2,32, 33 death‐associated protein kinase 1 (DAPK1) on 9q21–22,34 retinoic acid receptor ( RAR ) β 235 and topoisomerase II beta (TOP2B) on 3p2436 as representative genes contributing to tumor development. Of these candidate genes, we selected CDK4/6 and RARβ2 as genes involved in colorectal tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] We analyzed the combinatorial effects of palbociclib with the commonly used chemotherapy agents against CRC, as a prelude to possible translation. Chou-Talalay analysis revealed that palbociclib can synergize with a variety of chemotherapies under hypoxia (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…8 Synergy of palbociclib with a MEK inhibitor has also been demonstrated in KRAS mutant colon cancer in vivo. 9,10 Vemurafenib-resistant tumors remain sensitive to palbociclib suggesting that initial treatment with vemurafenib followed by palbociclib with or without mTOR inhibitors might provide an approach to overcome recurrence of vemurafenibresistant, metastatic tumors. 11 In brief, these studies indicate combinatorial administration of a CDK4/6 inhibitor with other chemo-or targeted-therapies could provide a promising treatment against various malignancies.…”
Section: Introductionmentioning
confidence: 99%